Digital Intelligence (DQ): Demands and Challenges in the Educational System - Leovigildo Lito Mallillin; Sammy Q. DOLBA (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
This study investigates the integration of Digital Intelligence (DQ) within the modern educational system, identifying it as both a critical demand and a significant challenge. The research explores four key dimensions: the demands and challenges of DQ, the conceptual definition and competencies of DQ, institutional preparation, and the practical integration of DQ in learning environments. Adopting a qualitative research design, the study conducted in-depth analysis through the participation of thirty (30) purposefully selected respondents. Results indicate that the demands of DQ require the embedding of digital literacy, digital creativity, and digital safety into curriculum tools and resources. DQ is defined as a holistic set of social, emotional, and cognitive abilities that empower both lecturers and students to navigate the digital world responsibly. Regarding preparation, the study highlights the necessity of institutional readiness, particularly in strengthening Information and Communication Technology (ICT) curriculum policies and digital literacy programs. However, the integration process reveals a critical "digital inequality," characterized by outdated software, inconsistent internet connectivity, and unequal access to devices, which threatens to leave certain students behind. The study concludes that while DQ is essential for pedagogical advancement, addressing infrastructure disparities is a prerequisite for its successful implementation.